Peran Gender, Usia, dan Tingkat Pendidikan terhadap Organizational Citizenship Behavior (OCB) - Dewi, Rizka Melinda; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2016)
This study aims to explore the role of demographic factors, namely, gender, age, and education level on organizational citizenship behavior (OCB) by using gender, age, and level of education as the independent variables and organizational citizenship behavior (OCB). The study was conducted to follow up the difference in the results of the earlier study.Â  The research is important because OCB creates prosocial and constructive behavior that beneficial for the organization. OCB could be measured using Organizational Citizenship Behavior Checklist (OCB-C) that designed to measure the OCB scores of employee.